Characterization of a population of industrial direct labor workers for anthropometric studies. - Labrador, Alejandro (Conexiones UG, 2023)
Anthropometric investigations should have a population that takes into account the age group and sex, for this it is necessary to know the population or the number of individuals to be studied. Official entities such as the National Institute of Statistics (NIS) and in the industrialsector lack figures that can provide information that characterizes a population of Venezuelan industrial direct labor (PVIDL). The objective of this research was to characterize a PVIDL that allowed taking into account the current anthropometric variability in the Venezuelan industrial context. Methodology: A descriptive cross-sectional study was carried out with a survey or questionnaire, which made it possible to determine an approximate stratification of direct labor workers, which, as mentioned, does not exist sources or official data regarding PVIVL. Results: The Aragua state and its industrial zones were taken as the population base, obtaining the participation of 11 companies, duly chosen in the industrial zones. Within this survey, 3125 workers were obtained, being their stratification by sex in percentage: 80% men and 20% women, which was compared with the previous study of Burgos (2017). Conclusions: Within this study, the current characterization of a PVIDL is obtained, taking into account anthropometric variability: sex, age or age group and origin. Recommendations: Maintain and update thePMODIV data.
Keywords: age group; anthropometric variability; haracterization; industrial labor worker; sex